Taming national interests within the CFSP: Europe's cyber foreign and security policy as a test run - Annegret Bendiek; Max Becker; Camille Borrett; Paul Bochtler (Stiftung Wissenschaft und Politik (SWP), 2024)
The political debate over implementing qualified majority voting (QMV) into the Common Foreign and Security Policy (CFSP) is of high political relevance, especially given the shifting geopolitical landscape in Europe, including Russia's aggression against Ukraine and uncertainties regarding the US's engagement post-2024 elections. Germany, along with a group of other EU member states, is leading efforts to integrate a "sovereignty safety net" within the CFSP framework. This initiative is designed to ease the concerns of reluctant member states, by providing enhanced veto options for matters affecting national interests. Moreover, mechanisms like constructive abstention and the "passerelle clause" could be further exploited to facilitate common CFSP actions without requiring treaty reforms. Nonetheless, it is crucial that all measures designed to build political consensus for expanding the use of QMV within the CFSP, strike the right balance between national interests and European solidarity. This balance is essential for strengthening the EU's resilience and operational capability. Cyber foreign and security policy, with its transnational nature and need for swift and unified responses, presents a favorable testing ground for this approach.
Keywords: 320; Qualified majority voting; QMV; Common Foreign and Security Policy; CFSP; Common Security and Defence Policy; CSPD; constructive abstention; passerelle clause; Group of Friends; cybersecurity; cyberattacks; cyber diplomacy toolbox; CDT; European Peace Facility; Permanent Structured Cooperation; PESCO; EU Cyber Security Strategy; European Defence Union; Coordination Centre for the Cyber and Information Domain; Cyber Rapid Response Teams; European Repository of Cyber Incidents; EuRepoC; European Union Agency for Cybersecurity; ENISA; emergency brake; blocking minority; Ioannina mechanism; Passerelle-Verfahren